1996
DOI: 10.1097/00000542-199611000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Prolong Rat Sciatic Nerve Blockade In Vivo from Bupivacaine Microspheres

Abstract: Glucocorticoids prolong blockade from bupivacaine microspheres. The mechanism appears unrelated to the kinetics of bupivacaine release in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(141 citation statements)
references
References 21 publications
4
134
1
2
Order By: Relevance
“…doubling the number of hours by co-encapsulating dexamethasone (Colombo et al, 2005). In contrast, the addition of dexamethasone to 60 mm particles increases the duration of block from hours to days (Castillo et al, 1996;Kohane et al, 2003b), and the further addition of tetrodotoxin increases the duration to more than 9 days (Kohane et al, 2003b). Such durations of block could be difficult for smaller particles to achieve.…”
Section: Local Delivery For Local Therapymentioning
confidence: 99%
“…doubling the number of hours by co-encapsulating dexamethasone (Colombo et al, 2005). In contrast, the addition of dexamethasone to 60 mm particles increases the duration of block from hours to days (Castillo et al, 1996;Kohane et al, 2003b), and the further addition of tetrodotoxin increases the duration to more than 9 days (Kohane et al, 2003b). Such durations of block could be difficult for smaller particles to achieve.…”
Section: Local Delivery For Local Therapymentioning
confidence: 99%
“…Dexamethasone, a high-potency, long-acting glucocorticoid with little mineralocorticoid effect, has been shown to prolong peripheral nerve blockade in animals [5][6][7][8] and, when added to bupivacaine microspheres, to extend the duration of analgesia in humans [9,10]. Although incompletely understood, dexamethasone's mechanism of action may stem from decreased nociceptive C-fibre activity via a direct effect on glucocorticoid receptors [11] and inhibitory potassium channels [12].…”
Section: Introductionmentioning
confidence: 99%
“…They relive pain by reducing inflammation and blocking transmission of nociceptive c-fibres and by suppressing ectopic neural discharge [9]. Some study demonstrated the analgesic effect of systemic corticosteroid in combination with bupivacaine [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been done using dexamethasone 8 mg as an adjuvant to local anaesthetics mixture in brachial plexus block resulting in variable effects on onset but prolonged duration of analgesia [12][13][14][15][16][17][18][19][20][21] and motor block [13,17,18,21] In this context the present study has been undertaken to evaluate the efficacy of dexamethasone in the onset of sensory and motor blockade as well as duration of analgesia.…”
Section: Introductionmentioning
confidence: 99%